2016
DOI: 10.1007/s11307-016-0944-y
|View full text |Cite
|
Sign up to set email alerts
|

PET Imaging Study of S1PR1 Expression in a Rat Model of Multiple Sclerosis

Abstract: Purpose Upregulation of sphingosine-1-phosphate receptor 1 (S1PR1) expression in multiple sclerosis (MS) lesions is associated with neuroinflammatory response. This study investigated the correlation between neuroinflammation and S1PR1 expression in the spinal cord of an experimental autoimmune encephalomyelitis (EAE) rat model of MS, using the S1PR1 positron emission tomography (PET) radiotracer [11C]TZ3321. Procedures MicroPET imaging studies of [11C]TZ3321 were performed to measure uptake of [11C]TZ3321 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 44 publications
2
57
0
Order By: Relevance
“…5B&C). Similar Iba-1 positive cells distribution trend was found within both white matter and grey matter, which was consistent with previous report [21]. In white matter the number of Iba-1 positive cells reached the maximum (9.76 ± 1.19/100 μm 2 ) in EAE-P group then decline to 6.13 ± 1.30/100μm 2 in EAE-R group.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…5B&C). Similar Iba-1 positive cells distribution trend was found within both white matter and grey matter, which was consistent with previous report [21]. In white matter the number of Iba-1 positive cells reached the maximum (9.76 ± 1.19/100 μm 2 ) in EAE-P group then decline to 6.13 ± 1.30/100μm 2 in EAE-R group.…”
Section: Resultssupporting
confidence: 91%
“…Neuroinflammation plays a key role in the demyelinating pathogenesis of MS. The rat EAE model of MS includes acute severe neuroinflammation in lumbar spinal cord, with modest demylination, and has been used in our lab for evaluation of radioligands targeting neuroinflammation [21]. Noteably, [ 11 C]GSK1482160 showed 100 times lower binding affinity for the rodent P2X7 receptor versus the human P2X7 receptor (316 nM v.s.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of this signaling by an S1P1R agonist, such as fingolimod, has been effective in MS. Fingolimod reduces circulating T lymphocytes (including autoreactive ones), protects from neuroinflammation by blocking the effect of S1PR1 expression in astrocytes [24], and helps to regulate the blood-brain barrier [25]. In rats, a positron emission tomography imaging study showed how S1PR1 is upregulated in the lumbar spinal cord of EAE rats and associated with glial cell activation and immune cell infiltration [26]. It has been suggested that fingolimod might exert its action via this dual central-peripheral mechanism [27] and also through modulation of the Treg/Th17 cell balance by regulation of the Akt-mTOR and MAPK/ERK pathways [28].…”
Section: Discussionmentioning
confidence: 99%
“…Our group previously reported the radiosynthesis of [ 11 C]TZ3321, which has a nanomolar binding potency and good selectivity for S1PR1 [16]. [ 11 C]TZ3321 has been validated in three rodent models of inflammation: a mouse wire-injury model of neointimal hyperplasia [16], a rat EAE model of multiple sclerosis [32], and a rat carotid injury model of acute vascular inflammation [33]. In the current study, we confirmed the specificity of [ 11 C]TZ3321 by in vitro autoradiography in human femoral plaque tissue and further validated the radioligand in the ApoE −/− mouse model of atherosclerosis for detecting the plaque.…”
Section: Discussionmentioning
confidence: 99%